Imposition of Sanctions For Regional Heads For Disclaimer of Violations of The Covid 19 Health Protocol - Vania Chrisdiana Rejeki; Habib Adjie (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Covid pandemic has been determined by WHO which has an impact on all countries around the world, the impact of Covid 19 is not only on the global economic sector but on the social and cultural sectors as well. To prevent and combat this pandemic, it is necessary to enforce legal rules regarding health protocols by the central and local governments along with the participation of the community to make Indonesia free from Covid 19. It was found that there were still violations of the Covid 19 health protocol committed by the community, the regional head as the holder. regional authorities are liable for violations of health protocols.